Pushing the limits disabled dykes produce culture - Tremain, Shelley (Women's Press, 2009)
Cet impressionnant recueil de prose, de poésie, de chansons et d'art visuel rédigé par des lesbiennes handicapées est la première de deux anthologies liées (la seconde est un recueil d'essais). Dans son introduction percutante (« Nous sommes ici. Nous sommes handicapés et queer. Habituez-vous-y »), la rédactrice en chef Shelley Tremain appelle à la reconnaissance et à la compréhension du monde selon les lesbiennes handicapées. La collection elle-même est colérique, compatissante, drôle et surtout émouvante. Sherree Clark présente des extraits de son recueil de poésie et d'art Living with Arthritis. Margot K. Lane célèbre la sexualité dans un merveilleux poème intitulé « Full day ». Le récit posthume de Kathleen Martindale sur le cancer du sein est un appel à l’action contre le personnel médical insensible, tout comme la chronique de Kathleen Rockhill sur sa guérison d’un accident de voiture dévastateur. Combinant colère et célébration, Pushing the Limits est une révélation.
Keywords: amériques; anthologie; approches et analyses; arts; canada; capacitisme; corps; lesbianisme; littérature; outils; ouvrages de références; patriarcat; personnes lesbiennes; poésie; queer; racisme; ressource en ligne; régions géographiques; santé; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

Mental illness as social product or social construct: a contradiction in feminists’ arguments? - Busfield, Joan (Sociology of Health & Illness, 2008)
Feminists have been taken to task for suggesting both that the higher level of mental illness observed in women is a consequence of the oppression they face - an oppression which drives them into madness and mental disorder - and also that the concept of mental illness is a social construct inappropriately and incorrectly applied to women by a patriarchal order as a means of social control. This paper examines this supposed contradiction and the ideas that underly the contrasting contentions. It argues that the two positions are not in fact incompatible.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; angleterre; approches et analyses; cours; discipline; europe; inégalités; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; santé mentale; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Intersex: a perilous difference - Holmes, Morgan (Susquehanna University Press, 2008)
As threatening evidence that sex is not the natural basis upon which oppositional gender roles are built, the intersexed are made to disappear into normative categories, thus aligning once again the rightful place of male and female as opposites.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; intersexuation; patriarcat; personnes intersexes; premier cycle; santé; sciences humaines; soc2014; sociologie; système médical; systèmes d'oppressions; thématiques; violences; violences médicales

Les femmes, l’environnement et le développement durable - Braidotti, Rosi; Charkiewicz, Ewa; Häusler, Sabine; Wieringa, Saskia (Genre, mouvements populaires urbains et environnement, 2007)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; discours dominant; environnement; histoire et politique; inégalités; patriarcat; projet charge mentale; périodes historiques; racisme; ressource en ligne; santé; systèmes d'oppressions; thématiques; écoféminisme

Fonction sexuelle masculine et sexualité féminine - Giami, Alain (Communications, 2007)
Major changes have occurred in male and female sexual function/dysfunction research and treatments. Male erectile dysfunction has been re-conceptualized as an organic dysfunction, which marks a dramatic shift from previous conceptions of psychogenic impotence developed during the 60' and the 70's. This shift is based on major scientific discoveries, and pharmacological advances that took place since the early 80's under the influence of North American urologists. The release of sildenafil in 1998 was thecorner stone of a new paradigm of treatments focusing on male penile activity, far remote from any psychological approaches. More recently, the same group of urologists started to reconsider Female Sexual Dysfunction using the same organic/biological model of sexual function. New pharmaceutical products are currently under trial for the treatment of this new category of female sexual disorder. But as opposed to the absence of public adverse reaction to the development of this approach of male function, many voices raised to oppose this new conception of female function. A major discussion took place in the British Medical Journal (2003) stating that female sexual function was not organically driven, but rather determined by the social, psychological and interpersonal context of female sexual activity and relations. One of the major dimension of this discussion opposed the so-called "simplicity" of male sexual function to the "complexity" of female sexual function.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; essentialisme; europe; féminisme radical; patriarcat; premier cycle; pédagogie; périodes historiques; recherche; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Female Sexual Dysfunction: A Case Study of Disease Mongering and Activist Resistance - Tiefer, Leonore (PLoS Medicine, 2006)
"Tiefer highlights key steps in the ""creation"" of a new diagnosis, female sexual dysfunction, and of the campaign to challenge its reductionist approach to women's sexual problems. "
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; corps; cours; discipline; discours dominant; inégalités; patriarcat; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

La santé est politique - Vuille, Marilène; Rey, Séverine; Fussinger, Catherine; Cresson, Geneviève (Nouvelles Questions Feministes, 2006)
Keywords: 1900-1909; 1900-1999; 1970-1979; 1980-1989; 1990-1999; allemagne; approches et analyses; care; corps; cours; discipline; europe; france; inégalités; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; soc2051; sociologie; suisse; systèmes d'oppressions; thématiques; travail

Un âge critique. La ménopause sous le regard des médecins des XVIIIe et XIXe siècles - Tillier, Annick (Clio. Femmes, Genre, Histoire, 2005)
Si l’on possède peu de témoignages sur la manière dont les femmes du XIXe siècle ont vécu le vieillissement, les discours des médecins sur cette question abondent. La ménopause est décrite par eux comme une période particulièrement dangereuse qui, à l’instar de la puberté, bouleverse toute l’économie de la femme. Au nombre des maladies qui sont susceptibles de l’assaillir lorsque s’interrompt le mécanisme régulateur que représentait la menstruation s’ajoute la blessure narcissique que provoque la perte de sa féminité et l’entrée dans l’âge de décrépitude. Plus encore, la femme perdant avec la faculté d’engendrer sa vocation sociale (la maternité), cette période, souvent qualifiée d’âge critique ou d’âge dangereux, s’annonce comme une véritable mort sociale. Privée de sa capacité de séduction, fragilisée par la révolution physiologique qui s’opère en elle, la femme, encouragée à se retirer d’un monde où elle ne peut plus briller, est plus que jamais assignée à la sphère privée.
Keywords: 1800-1899; 1900-1999; angleterre; approches et analyses; corps; corps des femmes; cours; discipline; discours dominant; europe; france; inégalités; justice reproductive; maternité; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

The Quest for Modern Manhood: Masculine Stereotypes, Peer Culture and the Social Significance of Homophobia - Plummer, David C. (Journal of Adolescence, 2001)
This paper explores the use of homophobic terms by boys and young men and the meanings they invoke when using them. Highly detailed interviews were conducted with young men from diverse backgrounds about their own experiences while growing up and their observations of schools, teachers, family and peers. Homophobia was found to be more than a simple prejudice against homosexuals. Homophobic terms like “poofter” and “faggot” have a rich developmental history and play a central role in adolescent male peer-group dynamics. Homophobic terms come into currency in primary school. When this happens, words like poofter and faggot rarely have sexual connotations. Nevertheless, far from being indiscriminate terms of abuse, these terms tap a complex array of meanings that are precisely mapped in peer cultures, and boys quickly learn to avoid homophobia and to use it decisively and with great impact against others. Significantly, this early, very powerful use of homophobic terms occurs prior to puberty, prior to adult sexual identity and prior to knowing much, if anything, about homosexuality. An effect of this sequence is that early homophobic experiences may well provide a key reference point for comprehending forthcoming adult sexual identity formation (gay or not) because powerful homophobic codes are learned first.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; australie; cours; discipline; homophobie; hétérosexisme; masculinité; nouvelle-zélande; océanie; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences